Konstitusionalitas Model Putusan Bawaslu dalam Penyelesaian Pelanggaran Administratif Pemilu - Yusuf, Muhammad Rifai; Hidayat, Syarif (Jurnal Hukum & Pembangunan, 2025)
As one of the institutions that carries out quasi-judicial functions in the field of general elections, Bawaslu could issue a decision through an adjudication process. In 2017, Bawaslu was criticized for its several decisions in the Sipol case held by the KPU for the registration of participants in the 2019 general elections, mainly because it was considered that Bawaslu equated its position with the Supreme Court by assessing that Sipol in the KPU Regulation was not in line with the Election Law. In 2024, decisions on election administrative violations appear to be softer or seem to avoid the same potential criticism. This study aims to analyze two issues systematically, first, what is the position of Bawaslu in the Indonesian constitutional system, especially in its function as a quasi-judicial institution and its relation with the judicial power holder, and second, whether the Bawaslu decision model as regulated by the Election Law can exceed its authority and equal its position with the Supreme Court in terms of judicial review. Regarding the first issue, Bawaslu as a quasi-judicial institution has a constitutional basis with its status as a state auxiliary organ that is currently prevalent in Indonesia. Regarding the second issue, the constitutional design does not allow Bawaslu to exceed its authority by issuing decisions as the Supreme Court does in terms of judicial review. Keywords: Bawaslu Decision, Constitutionality, Administrative Violations, Supreme Court